A retrospective analysis of 44 patients with granuloma annulare during an 11-year period from a tertiary medical center in south Taiwan - Yu-Wen Cheng; Wen-Chien Tsai; Fu-Chen Chuang; Erick Chern; Chih-Hung Lee; Chao-Hsiang Sung; Ji-Chen Ho (Wolters Kluwer Medknow Publications, 2016)
Background: Granuloma annulare (GA) is a benign, usually self-limited, inflammatory skin disease. Although there have been several studies that review pathoclinical features about GA, the relevant epidemiological study in Taiwan was lacking. The purpose of this study is to evaluate the pathoclinical features and treatment outcome of GA in Taiwan. Methods: This study was performed by retrospective review of medical records and pathological slides of the patients diagnosed as GA in a tertiary referral medical center in Taiwan. Fisher exact test was performed to compare remission rate between adults and children, treatment and nontreatment groups. Result: The study included 44 patients with GA: 23 male and 21 female. The incidence of GA showed a bimodal age distribution (peaks below 20 years and above 50 years). Localized type is most common, followed by generalized variant. Perforating GA is the rarest subtype and was exclusively found in children. The pathology of GA is characterized by necrobiosis (100%), palisading granuloma (81.8%), and mucin deposition (93.2%); 13.6% and 6.8% of GA patients had history of diabetes mellitus and dyslipidemia, respectively. Conclusion: In contrast to the reported studies, the incidence of GA showed a bimodal age incidence with slight male preponderance. Our patients had higher prevalence of diabetes mellitus than the general Taiwanese population but had no increase in incidence of dyslipidemia. Whether patients received treatment or not does not affect the disease outcome. Overall, children have better prognosis than adults.